2015
DOI: 10.1186/s12891-015-0557-7
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of acute and overuse musculoskeletal injuries among young conscripts: a population-based cohort study

Abstract: BackgroundMilitary service in Finland is compulsory for all male citizens and annually about 80% of 19-year-old men enter into the service. The elevated risk for many chronic diseases and loss of function among those who are inactive and unfit can be often detected already in youth. On the other hand, activity-induced injuries among young are true public health issue. The purpose of the present prospective cohort follow-up study was to evaluate predictive associations between acute or overuse injuries and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
74
1
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(105 citation statements)
references
References 76 publications
(87 reference statements)
2
74
1
8
Order By: Relevance
“…Earlier researchers 34,36 who aimed to identify risk factors for musculoskeletal injuries in military populations have commonly found body composition measures such as a high BMI to be risk factors for injury. However, we did not find that body fat percentage was a risk factor for injury and only observed a BMI difference in the spine-injury group.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier researchers 34,36 who aimed to identify risk factors for musculoskeletal injuries in military populations have commonly found body composition measures such as a high BMI to be risk factors for injury. However, we did not find that body fat percentage was a risk factor for injury and only observed a BMI difference in the spine-injury group.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, dozens of injury categories are used in different diagnoses in other countries (eg, Norway). Furthermore, the subgroup analyses indicated that the combined incidence rate of acute injury was higher than that of overuse injury, which is inconsistent with results from other countries 4. Acute injuries are generally categorised as acute if there is a sudden onset involving known trauma, while overuse-related injuries have a gradual onset without known trauma67–69 or appear during physical activities in a previously symptomless body part 70.…”
Section: Discussionmentioning
confidence: 91%
“…Other countries have reported varying incidence rates for military training-related musculoskeletal injuries in recruits. For example, the incidence rate in the British Army during 26 weeks of training was reported to be 48.6%2; the incidence rate in the Finish Army during 6 months of training was reported to be 78%4; the incidence rate in the Norwegian Army during 6–10 weeks of training was reported to be 23.20% 5. Overall, musculoskeletal injuries have been the main study object regarding training-related injuries,1–5 and differences in the incidence rate between countries may be due to differences in the course duration, course content and intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Repetitive exercises and imbalance between training and recovery may be predictive factors for injuries (1,2). On the other hand, moderate physical activity with no focus on high performance is important to prevent illnesses such as hypertension, diabetes type II, obesity and others (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, even recreational practitioners are not immune to sports injuries, especially if not properly guided/supervised (1,2). Previous studies have indicated high incidence of injuries related to recreational sports practices and physical activities (5,6).…”
Section: Introductionmentioning
confidence: 99%